The Hungaria population: A comparison between sub-groups. (January 2015) - Cañada-Assandri, M.; Gil-Hutton, R.; Ribeiro, A.O.
Abstract: To investigate if the two sub-groups in proper inclination found in the Hungaria region byMilani et al. (2010) could be characterized by physical parameters of the objects, we analyze two surfaces properties of the asteroids in the zone: the taxonomical distribution, obtained from the SDSS-MOC4, and the albedo distribution, taken from the WISE data. Our analysis suggests that both sub-groups are different. The asteroids with sin i p < 0.4 exhibit a majority of X-types objects and an excess of high albedo objects. In contrast, the objects with sin i p > 0.4 show a taxonomical distribution dominated by S-types asteroids and an albedo distribution without high albedo excess. Based on these results we propose that the sub-group in high proper inclination and dominated by S-types could be the primordial population while the high albedo excess observed in the other sub-group could be the consequence of a contamination in this region with a medium-belt object(s) that filled the Hungaria region with fresh X-types after suffering a catastrophic collision. Abstract : Highlights: We study surface characteristics of Hungaria asteroids with databases. We compare surface properties of two dynamically separated subgroups. The characteristics of that could be a background asteroids in the region have been described.